Foundations of design - Davis, Jeff (Wadsworth, Cengage Learning, 2013)
Covers the major topics in the fundamentals of design. This book features a selection of contemporary and graphic design examples that aid students in making connections from the principles of design through to a final work. It offers students real world examples, as well as the online peer review and instructor critique tool, Art Studio